Strategi Pembelajaran Daring Dengan Model Resitasi Berbasis Teknologi Bagi Siswa MI/SD - Isnaeni, Aisah; Fakhru Ahsani, Eva Luthfi (As-Sibyan, 2020)
4.0 Revolution eases people to get connected online. It also influences the education development that goes in line with the information and communication technology advancement. One of the most-contributing in education world is online learning. This research aims to (a) describe the online learning strategy concept, (b) describe the technology based recitation model for learners, and (c) analyze the implementation of the online learning with technology based recitation model in NU Nurul Haq Islamic School, Prambatan, Kudus. This research uses a descriptive qualitative model from the interview results held online and face to face. The findings showed that online learning was effective to be implemented in current technologized era. Then, to make online learning running smoothly, there is a need of technology based tasks that could facilitate the online learning promotion by considering social, affective, cognitive, and psychomotor aspect. It is in accordance to technology based recitation model that could foster students’ behaviors to seek and manage their information and communication. Furthermore, it could foster responsibility and discipline of the learners.